PENURUNAN MASA PELAYANAN JALAN AKIBAT KENDARAAN DENGAN BEBAN BERLEBIH - I Dewa Made Alit Karyawan; Hasyim; Khairul Faqihi (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2021)
Road damage is caused by several factors, namely: unstable subgrade, climate, poor drainage system, materials, and work processes that do not meet the requirements. Besides that, vehicle traffic loads have a greater effect. Normal traffic load can maintain life as design. Problems arise when many vehicles pass with loads that exceed the required load limit. This will reduce the service life. Therefore, strict supervision of the maximum load at the weighbridge requires special attention. Especially if the road is an arterial road that is dominated by freight vehicles. The effect of decreasing pavement service life due to overloading can be done by comparing the service life with normal load and overload. The research was conducted on a national road section, namely Jalan Raya Ahmad Yani, located in Narmada, West Lombok Regency. The analysis was carried out on secondary data, namely the number of vehicles entering the weighbridge and daily traffic on average in 2018 and 2019. The results of the analysis are the number of equivalent axle loads and the Vehicle Damage Factor (VDF) on each type of vehicle with normal loads or more using the Bina Marga Method. Furthermore, the design life reduction analysis is carried out based on the cumulative results of Equivalent Standard Axle Load (ESAL) under normal load and overload conditions. The results of the analysis show that the equivalent value or VDF of normal load vehicles is 385120.1870 and VDF overload is 643207.3800 so that the percentage increase in VDF value is 67.01% and there is a decrease in age of 3.1 years, with the planned age of 10 years.